Intertestualità (o quasi) lampedusiane - Fabrizi, Angelo (Cuadernos de Filología Italiana, 2007)
The essay focuses mainly on part VIII of Giuseppe Tomasi di Lampedusa’s novel Il Gattopardo, and on the writer’s ability to express complex meanings through a limited number of words or simply trough a single word (i. e. “cara”). Tomasi admired the so-called “scrittori magri”, authors whose prose was terse and disciplined, such as Stendhal and Jane Austen, and who are remembered for their unique allusive writing style. Although Tomasi falls in the category of descriptive writers, in his novel he show impressive syntetic skills that reflect nineteenth-century narrative models. After referring to Manzoni “lirico” (in a parodic sense) and to possible Montalian echoes, Tomasi’s ideological position is explored along with his reluctance to be a proponent for political ideals.